Terminologiske ressurser i Norge: nye brukergrupper og bruksområder - Kristian Våge, Ole (LexicoNordica, 2018)
Who are the end users of terminology resources, and in which areas are such resources employed? This article explores these questions in the handbooks of terminology and other seminal publications. Furthermore, the article identifies certain fields of application emerging in Norway, i.e. terminology resources in digitalization of the public sector, in language technology, in education, and in plain language measures.